Incidence of fungi in samples yerba mate in the department of Itapúa (Journal on studies and research of academic knowledge, 2021)
Human consumption of yerba mate in Paraguay is traditional and its demand is increasing, considering that it is a basic product of the food consumption of Paraguayan families. Yerba mate is a product highly exposed to the attack of contaminating microorganisms, mainly by the fungi found in the elaborated product, altering its content. Considering this problem, the research work was carried out with the aim of identifying the fungi present in the yerba mate samples composed of different commercial brands. The research was carried out in the Plant Pathology Laboratory of the Faculty of Agricultural and Forestry Sciences at the National University of Itapúa. A completely randomized design was used with 15 treatments that consisted of yerba mate samples of different brands. The fungus count was carried out using the surface dissemination method in chloramphenicol agar according to the methodology proposed in IRAM Standard 20517: 2004 and 2007. As a result, three genera associated with the yerba mate compound were identified: Aspergillus, Penicillium and Fusarium, all of them with incidence within the criteria established in the Paraguayan Standard for compound yerba mate NP 3500201 (5,000 CFU / g).
Keywords: Illex paraguariensis; Food safety; quantification of contaminating microorganisms